ANALISIS PENGGUNAAN CANVA SEBAGAI MEDIA PEMBELAJARAN DIGITAL PADA TEMA BUMIKU SAYANG, BUMIKU MALANG DALAM MENUMBUHKAN KEPEDULIAN LINGKUNGAN SISWA SEKOLAH DASAR - Kenusi, Afrilliana; Mayang Sari, Siti; Haekal, T.M. (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the use of Canva as a digital learning media in the theme “My Beloved Earth, My Ailing Earth” to foster students’ environmental awareness. The background of this research is based on the low level of students’ environmental awareness and the suboptimal use of digital media in the learning process. The study employed a qualitative approach with a descriptive research design. The subjects of this study were elementary school students involved in learning activities using Canva as a learning media. Data were collected through observation, interviews, and documentation. The results show that the use of Canva as a digital learning media enhances student engagement, facilitates better understanding of the material, and promotes environmental awareness. Therefore, Canva can serve as an effective alternative learning media to support environmental education in elementary schools.